Effect of Lithium Doping on the Structures and CO2 Adsorption Properties of Metal‐Organic Frameworks HKUST‐1. Issue 45 (4th December 2018) - Zhou, Lingling; Niu, Zhaodong; Jin, Xu; Tang, Lihong; Zhu, Liping
Abstract: The metal‐organic framework HKUST‐1 was modified by lithium doping to enhance its CO2 adsorption property. An optimal CO2 adsorption capacity was achieved as a lithium nitrate solution with a moderate concentration was used as the doping agent in the modified HKUST‐1. The chemical and crystalline structures of the modified HKUST‐1 were characterized in detail. It was found that the crystalline structures and morphologies of HKUST‐1 were well preserved after lithium doping. Also, the lithium doping did not deteriorate the thermal stability of HKUST‐1. Based on the experimental results of CO2 adsorption by in‐situ diffuse reflectance infrared Fourier transform spectroscopy, a possible mechanism of CO2 adsorption in the lithium doped HKUST‐1 was proposed. It is believed that the incorporation of lithium has enhanced the interaction between CO2 molecules and the metal‐organic frameworks. As a result, the CO2 adsorption capacity greatly increased. These findings and insights are helpful to the development of high‐performance materials for CO2 adsorption in the future. Abstract : The metal‐organic framework HKUST‐1 was synthesized and modified by lithium doping to enhance its CO2 adsorption property. And then the adsorption mechanism of carbon dioxide (CO2 ) on xLi/HKUST‐1 was studied by in‐situ diffuse reflectance infrared Fourier transform spectroscopy.